A closed-form fracture model to predict tensile strength and fracture toughness of alkali-activated slag and fly ash blended concrete made by sea sand and recycled coarse aggregate. (20th September 2021) - Yang, Shutong; Li, Linzhen; Sun, Zhongke; Wang, Junhao; Guo, Qianhui; Yang, Yushan
Highlights: New alkali-activated concrete made by sea sand and recycled aggregate is developed. Parameters representing material heterogeneity and discontinuity are quantified. Size-independent fracture parameters are linked to the maximum load analytically. Scatters in fracture parameters are analyzed based on normal distribution method. Fracture patterns of the tested specimens for the new concrete are clarified. Abstract: A new type of concrete, namely alkali-activated slag and fly ash blended sea sand recycled aggregate concrete (AASRAC), is developed in this paper. By considering its future service under ocean environment, crack resistance of the new concrete should be emphasized and evaluated rationally. Similar to ordinary concrete, however, size effect would be inevitable in the determined tensile strength and fracture toughness based on traditional continuum mechanics. To address this issue, the intention of this paper is to propose an analytical fracture model to predict the tensile strength f t, fracture toughness K IC and energy G F by using tests on three-point-bending notched beams of AASRAC. The average aggregate size d avg and two discrete numbers β and β w are introduced to represent the material heterogeneity and discontinuity, respectively. The critical effective crack propagation length and critical crack-tip opening displacement are quantified as the d avg multiplied by β and β w, respectively, when the maximum applied load F max is reached. Closed-form solutions of the size-independent f t, K IC and G F are then obtained by using the experimentally measured F max based on boundary effect model. The means, and upper and lower bounds of the fracture parameters with 95% reliability are determined from the normal distribution analysis. Results show that the fracture parameters can be yielded with reasonable accuracy if β  = 1.0 and β w  = 1.0. The predicted f t, K IC and G F are higher as the slag-to-fly ash mass ratio increases in AASRAC. The predicted f t based on the proposed model is significantly larger than the traditional splitting tensile strength. The main failure mode of the tested AASRAC beam is that about 80% of the recycled coarse aggregates are fractured due to the improved interfacial micro-structures between the mortar and aggregates. The proposed model can give a rational design method for the new concrete.